Apakah Selera Humor Menurunkan Stres? Sebuah Meta-analisis - Hartanti (ANIMA Indonesian Psychological Journal, 2008)
The result of meta-analysis on 42 effect sizes from 5.015 subjects show that sense of humor is negatively correlated to stress (r = –0.1251). The difference in variance of correlation can, among others, be caused by sampling error (13.100%) and error in measurement of independent as well as dependent variables (0.0440%).This small percentage shows that error deviation probably caused by sampling error and error in measurement of independent and dependent variables was very small. Although sense of humor has an positive impact to decrease stress, sometimes it’s the other way round, such as conflict between friends if humor is used at an improper time, situation, or goal. A rude humor which attacks other people doesn’t decrease but rather enhance tension and anger. Nevertheless, in general, sense of humor tends to decrease stress and is positive towards an individual’s physical as well as psychological health. Hasil meta analisis terhadap 42 ukuran efek dari 5.015 subjek menunjukkan bahwa selera humor berkorelasi negatif dengan stres (r = –0.1251). Perbedaan variasi korelasi dapat disebabkan antara lain karena kesalahan dalam pengambilan sampel sebesar 13.100% dan kesalahan dalam pengukuran variabel bebas maupun tergantung sebesar 0.0440%. Persentase yang kecil ini menunjukkan kemungkinan bias kesalahan karena kekeliruan dalam pengambilan sampel maupun pengukuran sangat kecil. Sekalipun selera humor berdampak positif untuk menurunkan stres, namun kadang-kadang justru menimbulkan efek negatif seperti konflik antar-teman bila humor digunakan pada waktu, situasi, dan sasaran yang tidak tepat. Humor yang kasar dan menyerang orang lain tidak mengurangi tetapi justru meningkatkan ketegangan dan kemarahan. Pada akhirnya, hasil meta menunjukkan bahwa selera humor cenderung menurunkan stres dan menimbulkan efek positif bagi kesehatan fisik ataupun psikis individu.